(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article deals with the study of ‘green architecture’ as a new format of architecture development, the future of sustainable design, its key principles that contribute to the harmonious combination of natural and artificial environments on the examples of modern trends in the design and construction of ‘green architecture’ objects, taking into account modern innovations. ‘Green architecture seeks to create environmentally friendly buildings that minimise energy and water consumption while maximising the use of renewable resources and recyclable materials. In recent years, ‘green architecture’, also known as sustainable architecture, has become an object of interest among architects, designers and investors alike. This trend is a consequence of the growing awareness of climate change and the need to reduce the environmental impact of the construction industry. The environmental problem has become relevant in all spheres of human life today. Humanity has become concerned about the preservation of natural resources and environmental issues. There is a need to find new ways to solve these problems. The purpose of the paper is to study green architecture, its key principles that contribute to the harmonious combination of natural and artificial environments. The main aspects of greening buildings, such as green facades and green roofs, are considered. Their benefits are discussed, such as improved air quality, reduced cooling and heating loads, and noise reduction both in the urban environment outside the building and in the environment of living, working or relaxing inside the building. Green architecture is a constantly evolving field that offers innovative solutions to reduce the environmental impact of the construction industry. These buildings not only set a new standard in construction, but also serve as inspiration for future sustainable architecture projects. The development of new materials and technologies continues to improve efficiency and reduce costs, making sustainable architecture an increasingly attractive option for construction projects around the world.